Implementasi Keterampilan Refleksi Perasaan Konseli Oleh Guru Bimbingan Konseling Dalam Konseling Individual - Anggraini, Eka Guslia; Sunaryo A.I (Jurnal Bimbingan dan Konseling Pandohop, 2021)
Reflection skills are techniques that focus the client's feelings on counseling sessions. So that the feeling of being doubtful or blurred can become clearer. The purpose of this study was to find out how the implementation of the reflection skills of BK teachers in SMKN-1 Palangkaraya in implementing individual counseling to students. In this study using the type of qualitative research that is explained in this study more clearly explained by the source of the data in this study must be saturated or it can be said that the statement in the study does not change. The sample in this study amounted to 12 people consisting of 4 BK teachers and 8 students. Data collection is done by interview, observation and documentation. The results showed that the SMKN-1 Palangkaraya teacher displayed feeling skills during counseling that began by listening carefully, interpreting the implied feelings, and formulating in clear sentences containing feelings. It was concluded that the BK teacher performed the skills to reflect feelings well, so that is what makes students often come to the BK room. Supported by students' statements during the interview after following counseling that they feel relieved and clearly understand their own feelings.